2014
DOI: 10.1002/term.1856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore sizes of PLGA scaffolds on mechanical properties and cell behaviour for nucleus pulposus regenerationin vivo

Abstract: This study investigated the influence of pore sizes of poly(lactic-co-glycolic acid) (PLGA) scaffolds on the compressive strength of tissue-engineered biodiscs and selection of the best suitable pore size for cells to grow in vivo. PLGA scaffolds were fabricated by solvent casting/salt-leaching with pore sizes of 90-180, 180-250, 250-355 and 355-425 µm. Nucleus pulposus (NP) cells were seeded on PLGA scaffolds with various pore sizes. Each sample was harvested at each time point, after retrieval of PLGA scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 34 publications
1
36
0
1
Order By: Relevance
“…Pore architecture, including pore size, porosity, pore wall architecture, and pore interconnectivity, is the feature that is highly controllable in polymers. From reviewed papers, 10 articles evaluated following features on behavior of various cell types . Two Studies by Pamula group have shown high degree of osteoblast infiltration and proliferation in PLGA scaffolds with pore size of 400–600 μm and porosity of around 83% and 88% .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pore architecture, including pore size, porosity, pore wall architecture, and pore interconnectivity, is the feature that is highly controllable in polymers. From reviewed papers, 10 articles evaluated following features on behavior of various cell types . Two Studies by Pamula group have shown high degree of osteoblast infiltration and proliferation in PLGA scaffolds with pore size of 400–600 μm and porosity of around 83% and 88% .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, they showed high osteoblast proliferation on both surface and inside the scaffolds with larger pore size (600 μm), whereas in PLGA with smaller pores (40 μm) fewer cells were observed only on the surface of scaffolds . Similarly, Kim et al showed that PLGA scaffolds with pore size of around 410 μm supported more neural cell, human nucleus pulposus cell, adhesion as well as ECM production . Vaquette et al fabricated PCL scaffold to create scaffolds with different pore size ranges (5–20 µm).…”
Section: Resultsmentioning
confidence: 99%
“…Fabrication of pristine PLGA scaffolds was achieved by following previously described procedures (Kim et al ., ; Ju et al ., ). Specifically, the lactide:glycolide ratio in PLGA was chosen as 75:25, because this combination was found to stably retain the 3D microporous morphology and had a fast in vivo degradation (Chant et al ., 1999; Wang et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Cultured media was removed and washed one time with PBS and then the staining was performed. All the samples were observed by inverted research microscope TE2000‐U (Nikon, Japan) 32 …”
Section: Methodsmentioning
confidence: 99%